The comparative effectiveness and cost-effectiveness of ranibizumab for neovascular macular degeneration revisited. Issue 1 (December 2017) - Brown, Gary; Brown, Melissa; Lieske, Heidi; Turpcu, Adam; Rajput, Yamina
Abstract Background To compare a near decade of follow-up, newer control cohort data, use of both the societal and third party insurer cost perspectives, and integration of unilateral/bilateral therapy on the comparative effectiveness and cost-effectiveness of intravitreal ranibizumab therapy for neovascular, age-related macular degeneration (AMD). Methods Value-Based Medicine®, 12-year, combined-eye model, cost-utility analysis employing MARINA and HORIZON clinical trial data. Preference-based comparative effectiveness outcomes were quantified in (1) QALY (quality-adjusted life-year) gain, and (2) percent improvement in quality-of-life, while cost-effectiveness outcomes were quantified in (3) the cost-utility ratio (CUR) and financial return-on-investment (ROI) to society. Results Using MARINA and HORIZON trial data and a meta-analysis control cohort after 24 months, ranibizumab therapy conferred a combined-eye patient value (quality-of-life) gain of 16.3%, versus 10.4% found in 2006. The two-year direct ophthalmic medical cost for ranibizumab therapy was 46, 450, a 33.8% real dollar decrease from 2006. The societal cost perspective CUR was −242, 920/QALY, indicating a 282, 517 financial return-on-investment (ROI), or 12.3%/year to society for direct ophthalmic medical costs expended. The 3rd party insurer CUR ranged from 21, 199/QALY utilizing all direct, medical costs, to 69, 591/QALY using direct ophthalmic medical costs. Conclusions Ranibizumab therapy for neovascular AMD in 2015, considering treatment of both eyes, conferred greater patient value gain (comparative effectiveness) and improved cost-effectiveness than in 2006, as well as a large monetary return-on-investment to the Gross Domestic Product and nation's wealth. The model herein integrates important novel features for neovascular age-related macular degeneration, vitreoretinal cost effectiveness analyses, including: (1) treatment of both eyes, (2) a long-term, untreated control cohort, and (3) the use of societal costs.